Aesthetic and functional rehabilitation with a fixed prosthetic denture in the primary dentition: A case report - Portilla Kirby, Miryam Jacqueline (2018)
Early Childhood Caries (ECC) is a disease of multifactorial etiology that affects the human being in the preschool stage, in a more aggressive level presents as severe caries in childhood (S-ECC) and has onset in the upper primary incisors. Patient, 4 years old female, on clinical examination presented multiple caries lesions, with diagnosis of pulp necrosis and fistulas in the primary upper incisors that were extracted, caries lesions on the upper lateral incisors without pulp involvement that were used as the pillars for the prosthesis, the treatment indicated was the construction and cementation of a fixed prosthesis of a tube-bar system, called Denari prosthesis, created by Dr. Walter Denari (UNISANTA- Brasil), which presents as main characteristics: Transversal growth of the upper jaw, it is fixed with the aim of avoiding losses on the part of the child, regain function and smile lost. It’s a minimal wear of dental pillars and is an alternative treatment that avoids alterations in speech, atypical swallows and restores the harmony of simple and efficient smile way in the patient.